Communications, Signal Processing, and Systems Proceedings of the 2018 CSPS Volume I: Communications - Liang, Qilian; Liu, Xin.; Na, Zhenyu; Wang, Wei.; Mu, Jiasong; Zhang, Baoju; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book brings together papers from the 2018 International Conference on Communications, Signal Processing, and Systems, which was held in Dalian, China on July 14-16, 2018. Presenting the latest developments and discussing the interactions and links between these multidisciplinary fields, the book spans topics ranging from communications, signal processing and systems. It is aimed at undergraduate and graduate electrical engineering, computer science and mathematics students, researchers and engineers from academia and industry as well as government employees.
Wireless communications -- Wireless networks -- Internet of Things -- Wireless sensor networks -- Signal processing for communications and networking -- Audio and acoustic signal processing -- Bio imaging and signal processing -- Machine learning for signal processing -- Sensor array and multichannel signal processing -- Design and implementation of signal processing systems -- Circuits and Systems for Communications -- Deep Learning -- Fuzzy Logic Systems -- Nonlinear Systems for Communications and Signal Processing.
Keywords: Telecommunication; Electronic circuits; Signal processing; Computer networks .; Computer science -- Mathematics; Communications Engineering, Networks; Electronic Circuits and Systems; Signal, Speech and Image Processing; Computer Communication Networks; Mathematical Applications in Computer Science